Comparação entre força muscular e flexibilidade dos membros inferiores de indivíduos com e sem Diabetes Mellitus tipo 2 - Bavaresco, Suzane Stella (2017)
Objective: This study´s objective was to compare the muscle strength and flexibility of the lower limbs of individuals with and without DM2. Method: Study of the type exposed and not exposed to DM2. 64 patients with and without diagnosis of Diabetes Mellitus Type 2 were included in the sample. It was also included individuals with medical diagnosis of DM2, referred to electromyography, and not exposed to DM2, recruited from ads at the participating hospital. And, as exclusion criteria, individuals over the age of 70; Individuals who for some reason failed to complete one or both tests. The sample was not probabilistic. Individuals who fulfilled the inclusion criteria manifested consent by signing the TCLE and the study evaluations were performed at FEFF / UPF. The numerical variables were described as medium ± standard deviation or median (percentile25 - percentile75) as they presented normal or nonnormal distribution. The numerical variables were expressed as absolute and relative frequency. The associations between exposure to DM2 or NDP and 1) age, height, body mass, body mass index and flexibility were evaluated using a variance analysis with a classification criterion and 2) sex and dominance using the Pearson´s Chi -square with continuity correction. The comparisons of the distribution of peak torque measurements among groups of individuals exposed and not exposed to diabetes or exposed to peripheral diabetic neuropathy were performed using covariance analyzes. Estimated medium torque peaks were reported, adjusted for age with their respective standard error estimates. It was considered as statistically significant values of probability <0.05. Results: The study population consisted of 64 individuals, 34 (53.1%) exposed to DM and 30 nonexposed, 50 (78.1%) were female, mean age was 60.7 ± 7.1 and the dominant lower limb was right in 57 (89.1%) of the individuals. The individuals exposed to DM were older, 62.8 ± 6 .73 vs 58.2 ± 6.94 years, p = 0.009 and with higher BMI, 29.82 ± 5.20 vs 27.99 ± 3.89 Kg / m², p = 0.027 than those not exposed to DM, respectively. Comparing individuals with and without a diagnosis of DM, we observed a reduction of the left flexion torque at a 120 ° angular velocity of diabetics compared to non-diabetic patients, 25.94 ± 2.26 vs 33.79 ± 2, 4 N / M, p = 0.027, respectively. The reduction of dorsiflexion torque on the right, at angular velocity of 60 °, was observed in diabetics compared to non-diabetic patients, 10.95 ± 0.89 vs. 13.95 ± 0.96 N / M, p = 0.033, respectively. When comparing diabetic individuals with and without a diagnosis of NDP, we observed a greater flexion deficit among neuropathic individuals when compared to non-neuropathic individuals, 46.57 ± 9.47 vs 11.63 ± 13.85 N / M, p = 0.049, respectively. Conclusion: No statistically significant differences were found when compared to groups exposed to and not exposed to DM2, and neuropathic and non-neuropathic diabetics.